A harmonic current detection algorithm for aviation active power filter based on generalized delayed signal superposition - Yong Lu; Bohan Li; Guofei Teng; Zhen Zhang; Xianfeng Xu (Scientific Reports)
Abstract To address the limitations of traditional harmonic detection methods for active power filters in variable-frequency-grids of the More Electric Aircraft (MEA), including inadequate filtering performance and poor adaptability to frequency variations, this paper proposed a harmonic detection algorithm tailored for active power filters in variable-frequency-grids of the MEA. Firstly, the filtering principle of the proposed operator is derived in detail, and its filtering characteristics and frequency adaptability are analyzed. Secondly, based on the proposed operator, a comprehensive harmonic current detection algorithm is designed to accommodate the wide frequency variation of variable-frequency-grids. Then, the complexity of the operator was analyzed. Due to the symmetry of the coefficients, the operation time of the operators can be reduced. Finally, experimental validation and comparative analysis with traditional harmonic detection methods are conducted. Experimental results demonstrated that the proposed harmonic current detection algorithm effectively detects harmonics in complex distorted current signals of aerospace power systems, confirming the algorithm’s accuracy, superior performance, strong robustness and practical applicability.